Diversifikasi Produk Olahan Berbahan Dasar Gula Merah Menjadi Aneka Minuman Bernilai Ekonomi Tinggi di Desa Borisallo Kec. Parangloe, Gowa - Munira Munira; Muhammad Arman; G. Gusnawati; D Darnengsih; Mustafiah Mustafiah; arfandi Ahmad; Nurhayati Rauf (Jurnal Pengabdian Pada Masyarakat, 2022)
Borisallo village is one of the villages that has the potential for sugar palm so some of its residents work as brown sugar farmers. Besides brown sugar, one of the potentialAnother interesting thing about this area is that the village of Borisallo is an axis road a district that connects the city of Makassar with the village of Malino which is a tourist attraction so along the axis road there are several restaurants. So it has the potential to create a small business of processed brown sugar which can boost the economy of brown sugar farmers. Solutions that offered to socialize the potential for processing brown sugar/palm into products ready-to-eat preparations, Conduct training in the manufacture of processed brown sugar in the form of various Cold Drinks (Milk -Brown Sugar, Milk Boba Brown Sugar, Milk Coffee Brown Sugar), conduct training on product packaging and marketing. After this PkM activity was carried out, the local brown sugar farmers have knowledge and skills in the technique of processing brown sugar productsinto other processed products with higher economic value and interest and motivation to carry out entrepreneurial activities. The entrepreneurial motivation initiated by the entrepreneurial starter kit that we provide is in the form of a set of tools beverage sealer/packaging. This tool will be managed by the Owned Enterprises Village (BUMDES) which will facilitate residents to do entrepreneurship